Classification And Functions Of Acehnese Riddles - Aina, Nandatul; Idaryani, Idaryani; Radhiah, Radhiah (Jurnal Penelitian Multidisiplin Bangsa, 2026)
This study investigated the classification and functions of Acehnese riddles used among Acehnese community in Bireuen District, Aceh, Indonesia. The interviews were held with 8 people from 2 two different villages in Bireuen district, Aceh province, Indonesia. Data were collected from participants as Indigenous Acehnese and Acehnese language is their mother tongue. The youngest participant is 33 years old and the oldest one is 85 years old. All participants are resided in Bireuen district. Since they did not travel much (except for occasional holidays with families and Hajj pilgrimage), they are deemed untainted native speakers of Acehnese. For analysis, grounded by the Conceptual Riddle Theory, this study found that the classification of Acehnese riddles and the functions of the riddles among Acehnese community use animals’ concept, living beings, human beings, inanimate entity, and plants. The functions of riddles are for entertaining, educational purpose, and logical reasoning. Most of the Acehnese riddles post the questions use living beings but undetected whether the living beings are human being or other kinds of living entities; animals or plants for example: ta ikat pijut, tapeuleuh tumbon (Tiep up thin, Released fat). The riddle is referred to mosquito net however, the entity is unpredictable until the answer is revealed.